One-dimensional water nanowires induced by electric fields. Issue 35 (28th August 2019) - Zhao, Wan; Huang, Haishen; Bi, Qingling; Xu, Yujia; Lü, Yongjun
Abstract : Water nanowires and structural evolution of hydrogen-bond networks under different electric fields. Abstract : Self-aggregation of water vapour molecules under external electric fields is systemically investigated by using molecular dynamics simulations. It is found that small water clusters aggregate into one-dimensional water nanowires along the electric field direction. The electric field strength plays a crucial role in tuning the nanowire structure. Under relatively weak electric fields such as E = 0.1 V Å −1, square and pentagonal prism-like structures are preferred; when intermediate strength electric fields are applied ( E = 1.0 V Å −1 ), water nanowires featuring a disordered mixture of four-, five- and six-membered rings are formed; and an open ordered structure which is reminiscent of two-dimensional (2D) ice is observed when the field strength becomes very high ( E > 3.0 V Å −1 ). Bond parameter analysis based on density-functional theory calculations shows that the electric field affects anisotropically the conformation of water molecules as well as the hydrogen-bond properties. Along the electric field, the H–O bond is stretched and the hydrogen bond shrinks with field strength in contrast to the changes perpendicular to the electric field. As a result, the hydrogen bonding is enhanced along the electric field. Under very high electric fields, the anisotropic hydrogen-bond network opens up via breaking of the bonds perpendicular to the electric field and ultimately relaxes into a loose quasi-2D ordered network.